(untitled) (Географический вестник=Geographical bulletin, 2017)
Сокращение лесных угодий в Пермском Прикамье в результате деятельности человека началось в XVI в. и продолжалось до середины XX в. С 80-х гг. прошлого века устойчивой тенденцией становится увеличение площадей, занятых лесами. В бассейнах Колвы, Ирени, Сарса и некоторых других рек Пермского Прикамья процесс преобразования бывших сельхозугодий в лесные геосистемы единовременно охватывал десятки тысяч гектаров. В горных территориях в последние десятилетия прирост лесных площадей в результате повышения границы произрастания криволесий и сомкнутых лесов происходит направленно со скоростью, обеспечивающей около 10% общего прироста лесистости в регионе. VARIATION OF FOREST COVER IN PERM PRIKAMYE (XVI–XXI centuries) Reduction of forest land in Perm Prikamye as a result of human activities began in the XVI century. And lasted until the middle of XX century. Stable trend is an increase in forest areas since the end of XX century. The process of converting the former farmland into forest geosystem once covered thousands of hectares in the basins of Colva, Irene, Sars and some other rivers Perm Prikamye. As a result of increasing growth boundaries elfin and closed forests in mountain areas is directed growth forest area. The rate of increase is 10% of the total increase forest cover in the region. K e y w o r d s: dynamics of forest cover; farmland; remote sensing.